THE ROLE OF ACCOUNTING INFORMATION SYSTEMS AND INFORMATION TECHNOLOGY IN IMPROVING THE QUALITY OF SME FINANCIAL REPORTS IN COLOMADU DISTRICT - Shelly Nur Oktavia; Meinaya Shafa Maura; Maryana Angi Pratiwi; Erlinta Sheila Mahendra (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of Accounting Information Systems (AIS) and Information Technology (IT) on the quality of SME financial reports in Colomadu District. Using a quantitative approach, primary data was obtained through a questionnaire distributed to 105 respondents (SME owners or employees in Colomadu District) and analyzed using multiple linear regression. The results show that, partially, AIS has a positive and significant effect with a t-value of 6.416. Similarly, IT shows a positive and significant effect with a t-value of 4.506. Simultaneously, these two variables contribute 67.8% to improving the quality of financial statements. These findings confirm that even though 50% of business actors still use manual systems, strengthening accounting systems and adopting technology has been proven to improve the reliability and accuracy of MSME financial reports in Colomadu District.